Mortalidade fetal e neonatal canina - Tayse Domingues de Souza (2017)
Canine fetal and neonatal mortality is responsible for many losses to breeders and dog owners. Many researchers consider infectious diseases as important causes of death, but epidemiologic investigations are limited to some breeds or kennels and had not been performed in Brazil before. The goal of this study was to investigate diseases related to canine fetal and neonatal mortality through anatomopathological, microbiological, and molecular analysis. A total of 203 puppies were submitted to necropsy, from 89 litters and 32 kennels located in the State of Espirito Santo, southeastern Brazil. Inflammatory lesions predominated, frequently with visualization of bacterial agents in tissue lesions by microscopy and/or their detection by the complementary analysis. Lesions most frequently diagnosed were pneumonia (85,4%), omphalitis (56,3%), hepatitis (47,2%), epicarditis (38,5%), glossitis (21,1%), and myocarditis (17,4%). Malformations were diagnosed in 7,5% of puppies. Post mortem changes prevented morphologic diagnosis in 15 animals. Freezing artefacts jeopardized microscopy in 51 animals. Bacterial infections were the main cause of death, mainly as secondary but also as primary infections. Bacterial agents isolated more frequently were Staphylococcus sp. (62,6%), Escherichia coli (36,0%), Klebsiella pneumoniae (17,8%), and Enterococcus sp. (9,8%). Isolation of more than one bacterial genus occurred in many puppies (55,8%). Polymerase chain reaction detected positivity in puppies for Brucella (21%), canine herpesvirus (1,5%), and Leishmania infantum (1,5%). Canine brucellosis was spread in puppies and kennels, although the frequency of abortions of infected litters was low (1/31). This study brings evidence that canine perinatal brucellosis was mainly related to stillbirth and neonatal death in the positive kennels studied, while abortion was rare in this population. Brucella-PCR positive puppies submitted to immunohistochemistry presented wide tissue distribution of the agent, frequently associated with opportunistic bacterial infection, especially with Staphylococcus (54%) and Escherichia coli (40,5%). Among viral agents, herpesvirus generalized infection occurred in only one neonate. A viral infection characterized by gastroenteritis, glossitis, and ulcerative dermatitis with intranuclear inclusions suggestive of viral infection was detected in 60/161 (37,3%) of puppies submitted to histopathology, always in association with opportunistic bacterial infection. It was not possible to identify the etiologic agent of these lesions with the methods employed in this research. One case of neonatal babesiosis due to Babesia canis vogeli infection was diagnosed through anatomopathological and molecular methods. Toxocara canis antigens were detected through immunohistochemistry in foci of necrotizing and granulomatous hepatitis, portal hepatitis, and interstitial pneumonia, suggesting visceral larvae migration. Adult T. canis worms were also detected in intestinal lumen of three neonates, nine to 20 days old. Co-infections were the cause of death of the fetuses and neonates in this study, mainly due to association between opportunistic bacterial agents, viruses, and Brucella sp. Opportunistic bacterial infections are easily diagnosed by routine methods and may hide the primary disease if analysis are not accurate or directed towards specific agents as Brucella and viruses. The infections diagnosed in the fetuses and neonates in this study, in many cases, were morphologically distinct from that described for dogs in other age ranges and poorly documented in the literature, what may lead to underdiagnoses and misdiagnosis in many cases. Anatomopathological characterization of canine perinatal diseases is the main contribution of this study.